Erythrocyte Sedimentation Rate and Hemoglobin Levels in Pesticide Poisoning-Farmers - Heru Cahjono; Salmon Charles P.T. Siahaan; Ferdinand Aprianto Tannus; Rizki Perdani; Eko Suhartono (Universitas Wijaya Kusuma Surabaya, 2022)
Pesticides are chemicals used to control insects, fungi, weeds, and others. Unrestrained use of pesticides leads to poisoning that has an impact on inflammation and anemia. To provide evidence for this notion, acetylcholinesterase enzyme levels, blood sedimentation rates, and blood hemoglobin levels of farmers exposed to pesticides have been studied. The study design was quantitative in a cross-sectional manner. The participants of the study were all members of the Kurnia Makmur farmer group in Landasan Ulin Utara District, Banjarbaru with a total sample of 60 people. An examination of acetylcholinesterase, erythrocyte sedimentation rate (ESR), and hemoglobin enzyme levels was carried out at the Banjar Regency Health Lab. The blood sample was withdrawn from the cubital vein. Spectrophotometry was used to determine acetylcholinesterase enzyme levels, while ESR was determined by the automatic method. Hemoglobin levels are measured by the cyanmethemoglobin method. T-tests were used to compare acetylcholinesterase, ESR, and hemoglobin levels in the normal group and the poisoning group. The study concluded that exposure to a pesticide in farmers' pesticide poisoning may cause inflammation characterized by an increase in ERS. However, there was no decrease in hemoglobin levels.